2013
DOI: 10.1002/adhm.201370014
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide: Purified Graphene Oxide Dispersions Lack In Vitro Cytotoxicity and In Vivo Pathogenicity (Adv. Healthcare Mater. 3/2013)

Abstract: Preparation of a high dispersibility graphene oxide (GO) that can be reliably used in biological investigations is reported by Kostas Kostarelos and co‐workers . Exposure of cells and tissue to the graphene oxide indicated a lack of cytotoxic responses in human cell cultures (in vitro) and after injection to living animals (in vivo).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…40 Dose‐dependent toxicity on cells was observed (i.e., 3–100 μg mL −1 concentration). An opposite result was reported in two independent studies showing that GO induced only a slight decrease on proliferation of the A549 cell line without signs of apoptosis or cell death in a range of concentrations between 7.8 and 200 μg mL −1 4143. The same material, treated with hydrazine to generate rGO, resulted instead in high cytotoxicity, thus significantly lowering the viability of the same type of cells 41…”
Section: In Vitro Effects Of Gfnsmentioning
confidence: 63%
See 2 more Smart Citations
“…40 Dose‐dependent toxicity on cells was observed (i.e., 3–100 μg mL −1 concentration). An opposite result was reported in two independent studies showing that GO induced only a slight decrease on proliferation of the A549 cell line without signs of apoptosis or cell death in a range of concentrations between 7.8 and 200 μg mL −1 4143. The same material, treated with hydrazine to generate rGO, resulted instead in high cytotoxicity, thus significantly lowering the viability of the same type of cells 41…”
Section: In Vitro Effects Of Gfnsmentioning
confidence: 63%
“…49 In contrast, the presence of contaminants as unreacted graphite oxide or graphitic fractions might be also responsible for inflammation. Indeed, when GO is extensively purified using several washings and centrifugation steps it did not show an increase in the level of proteins and polymorphonuclear leukocytes on days 1 and 7 after peritoneal administration (injected dose of 50 μg per animal) 43. No collection of giant cells, inflammatory response, and formation of granuloma were evidenced in comparison to long pristine multiwalled carbon nanotubes (Figure 5).…”
Section: In Vivo Effects Of Gfnsmentioning
confidence: 97%
See 1 more Smart Citation
“…[343] Also few researchers have recently found that pure and highly dispersable GO with 1-2 nm in thickness did not show any inflammatory response or granuloma formation at the mesothelial membrane after intraperitoneal injections. [344] Though there are no sufficient number of works available regarding the cytoxicity of graphene and braphene-based materials, [345] it is evident that different graphene and graphenebased materials will have a varying toxicological profile. There will be different conditions and effects when once exposed and also various factors are to be addressed and carefully noted before deriving to a valid conclusion.…”
Section: Toxicity Of Graphene and Graphene-based Materialsmentioning
confidence: 99%
“…It should be noted that the commercially available graphene ‘ nanoplatelet’ materials were not chemically or surface modified, therefore presumably hydrophobic and not very well dispersed. Some of us have recently reported that pure and highly dispersable GO with 1–2 nm in thickness and below 500 nm in lateral dimensions show no inflammation or granuloma formation at the mesothelial membrane after intraperitoneal injections 87. The most important in vivo studies investigating the toxicological side effects of graphene using in vivo models are shown in Table 4 .…”
Section: Toxicity and Biocompatibility Of Graphene Materialsmentioning
confidence: 99%